The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1097/00001888-199409000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Family practice graduate medical education and hospitalsʼ patient care costs in New Jersey

Abstract: These findings suggest that family practice residencies do not add to the direct inpatient costs of teaching hospitals, and in certain instances may even reduce hospital patient care costs. In times of increasing cost consciousness in health care and medical education, this provides a further rationale for institutions to sponsor graduate training in family practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 5,6 The type of residency program may also be important: one study in New Jersey found that hospitals with family practice residencies had lower inpatient costs compared with nonteaching hospitals or with hospitals sponsoring other types of training programs. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5,6 The type of residency program may also be important: one study in New Jersey found that hospitals with family practice residencies had lower inpatient costs compared with nonteaching hospitals or with hospitals sponsoring other types of training programs. 7 …”
Section: Discussionmentioning
confidence: 99%
“…5,6 The type of residency program may also be important; one study in New Jersey found that hospitals with family practice residencies had lower inpatient costs compared with nonteaching hospitals or with hospitals sponsoring other types of training programs. 7 These interinstitutional comparisons have attributed increased use of resources at teaching hospitals in part to the inexperience of residents. However, one study specifically refuted this explanation by finding similar resource utilization among teaching patients admitted early and late in the academic year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of resident care on costs of hospitalization has been well studied, although infrequently with consideration of reimbursements generated by that care 1–3 . We recently reported that patients on an internal medicine inpatient teaching service generated payments to the sponsoring community hospital that were higher, on average and for most diagnosis‐related groups (DRGs), than payments for nonteaching patients.…”
mentioning
confidence: 99%
“…These adjustments are difficult to make, 6 7 but when attempts are made the difference between teaching and non-teaching hospitals is diminished. 8 9…”
mentioning
confidence: 99%